Outcomes of evaluation and testing of 660 individuals with hearing loss in a pediatric genetics of hearing loss clinic. Issue 10 (2nd August 2016) - Mehta, Devanshi; Noon, Sarah E.; Schwartz, Emily; Wilkens, Alisha; Bedoukian, Emma C.; Scarano, Irene; Crenshaw, E. Bryan; Krantz, Ian D.
Abstract : Hearing loss is a relatively common condition in children, occurring in approximately 2 out of every 1, 000 births with approximately 50% of reported diagnoses having a primary genetic etiology. Given the prevalence and genetic component of hearing loss, coupled with a trend toward early diagnosis with the institution of universal newborn hearing screening, The Genetics of Hearing Loss Clinic was established at The Children's Hospital of Philadelphia to manage the diagnosis, testing, and genetic counseling for individuals and families. This paper described a cohort of 660 individuals with a diagnosis of hearing loss evaluated between July 2008 and July 2015 in the Genetics of Hearing Loss Clinic. To elucidate the cause of hearing loss in this cohort for better management and prognostication, testing included single nucleotide polymorphism chromosomal microarray, hearing loss next generation sequencing panel, and additional clinical tests inclusive of thyroid and renal function studies, temporal bone magnetic resonance imaging, and electrocardiogram. Of those evaluated, most had bilateral sensorineural hearing loss, occurring in 489/660 (74%). Additionally, 612/660 (93%) of patients presented with a nonsyndromic form of hearing loss (no other observed clinical findings at the time of exam), of which pathogenic mutations in GJB2 were most prevalent. Of the individuals with syndromic manifestations (48/660), Usher and Waardenburg syndrome were most commonly observed. A family history of hearing loss (first degree relative) was present in 12.6% of families with available information. Through molecular analyses, clinical examination, and laboratory testing, a definitive etiologic diagnosis was established in 157/660 (23.8%) of individuals. © 2016 Wiley Periodicals, Inc.